2022
DOI: 10.3390/biom12020154
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Alternative Splicing Events in Porcine Skeletal Muscles with Different Intramuscular Fat Contents

Abstract: Meat quality is one of the most important economic traits in pig breeding and production. Intramuscular fat (IMF) is a major factor that improves meat quality. To better understand the alternative splicing (AS) events underlying meat quality, long-read isoform sequencing (Iso-seq) was used to identify differential (D)AS events between the longissimus thoracis (LT) and semitendinosus (ST), which differ in IMF content, together with short-read RNA-seq. Through Iso-seq analysis, we identified a total of 56,789 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…2 C) (Additional file 5 : Table S4) were identified. Notably, a very small fraction of DASGs was differentially expressed, consistent with the previous reports [ 33 35 ]. This suggested that the dynamic AS change in genes has potential to affect muscle heterogeneity in addition to gene dysregulation.…”
Section: Resultssupporting
confidence: 92%
“…2 C) (Additional file 5 : Table S4) were identified. Notably, a very small fraction of DASGs was differentially expressed, consistent with the previous reports [ 33 35 ]. This suggested that the dynamic AS change in genes has potential to affect muscle heterogeneity in addition to gene dysregulation.…”
Section: Resultssupporting
confidence: 92%
“…A total of six libraries were prepared from the experimental and control groups, each with three replicates. The libraries were prepared and sequenced on a NovaSeq 6000 sequence analyzer (Illumina, San Diego, CA, USA) by the Frasergen company (Wuhan, China), as described previously [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The transcript assembly and quantification in fragments per kilobase million (FPKM) were performed with Cufflinks (v2.2.1) [ 36 ]. The threshold for expression was set at FPKM > 0.1 in at least one sample, as used previously [ 33 ]. The gene expression levels were compared between groups with DESeq2 (v1.22.2) [ 37 ], and DEGs were identified according to the criteria of absolute Log2-foldchange > 1 and p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The AS events of precursor messenger RNA (pre-mRNA) occur due to the involvement of five small nuclear ribonucleoprotein (snRNP) complexes in the removal of introns [ 21 ]. In general, AS events display five patterns: exon skipping (ES), intron retention (IR), mutually exclusive exons (MEE), alternative acceptor site (AAS), and alternative donor site (ADS) [ 22 ]. Previous studies have indicated that the AS is associated with the regulation of proliferation [ 23 ], differentiation [ 24 , 25 ], and apoptosis [ 26 ] of the cell.…”
Section: Introductionmentioning
confidence: 99%